Penyuluhan Penggunaan Dan Pemanfaatan Sosial Media Bagi Masyarakat Pulau Lance Batam - Maldin, Siska Amelia; Silitonga, Frangky; Sianipar, Baktivillo; Kartika Cahayani; Senop Putra Perwira; Ayu Dara Tista; Ardiansyah Saputra (PUSLITABMAS-Politeknik Pariwisata Batamc, 2024)
This Social Community is carried out to enable lecturers and students together with the community to find the best solutions that can answer the problems experienced by the community, especially in the use of social media as a marketing tool for tourism activities which can be part of the driving force for improving the economy of Lance Island residents. This PKM activity has inspired the Lance community that Lance Island has its own attraction to be marketed using residents' social media in tourism development as part of an opportunity to improve the welfare of the Lance Island community. From this PKM activity, an understanding of the important thing that the tourism area must have networks and upgrade its ability to see tourism opportunities that are of interest will be produced while still prioritizing the cultural wisdom that exists on Lance Island. This activity consists of students and lecturers carrying out their tri dharma